To solve the system of equations given by:
- \( x = 6y - 3 \)
- \( 2x + 7y = 13 \)
we can substitute equation (1) into equation (2).
Substituting \( x \) in equation (2):
\[ 2(6y - 3) + 7y = 13 \]
Now, distribute \( 2 \):
\[ 12y - 6 + 7y = 13 \]
Combine like terms:
\[ 19y - 6 = 13 \]
Now, add \( 6 \) to both sides:
\[ 19y = 19 \]
Now, divide by \( 19 \):
\[ y = 1 \]
Now that we have \( y \), we can substitute it back into equation (1) to find \( x \):
\[ x = 6(1) - 3 \] \[ x = 6 - 3 \] \[ x = 3 \]
Thus, the solution to the system of equations is:
\[ (x, y) = (3, 1) \]
To verify, substitute \( x = 3 \) and \( y = 1 \) into the second equation:
\[ 2(3) + 7(1) = 6 + 7 = 13 \]
Since both equations are satisfied, the solution \( (3, 1) \) is correct.